A Novel Active Polyphase Filter Employing Frequency-Dependent Image Rejection Enhancement Technique - Yue Yin; Haobo Qi; Haodong Lu; Ziting Feng; Jiayu He; Xinbing Zhang; Lei Li; Xiaofei Qi; Xiyuan Feng (Micromachines)
In low intermediate frequency (low-IF) receivers, image interference rejection is one of the core tasks to be accomplished. Conventional active polyphase filters (APPFs) are unable to have a sufficient image rejection ratio (IRR) at high operating frequencies due to the degradation of the IRR by the amplitude and phase imbalances produced by the secondary pole. The proposed solution to the above problem is a frequency-dependent image rejection enhancement technique based on secondary pole compensation. By adjusting the dominant pole frequency of the high-pass filter (HPF) appropriately, the proposed technique can theoretically completely reject the image interference signal even in the presence of the secondary pole. The proposed APPF is simulated and fabricated in a 180-nm CMOS process. The simulation results show that the proposed technique can improve the IRR of the APPF by more than 30 dB at the operating frequency of hundreds of MHz. The measured IRR is better than −31 dB at the frequency from 95 to 105 MHz. Unlike conventional schemes, the proposed design is from the perspective of frequency correlation, which makes the operating frequency no longer limited by the secondary pole frequency. In addition, the proposed design also has an excellent IRR for quadrature input signals with phase imbalance.